Serum uric acid to creatinine ratio and long-term target vessel events in diabetes patients undergoing PCI with drug-eluting stents implantation: a retrospective study - Cui, Penghui; Wang, Shuting; Zhang, Zherui; Wang, Ruihua (Frontiers in Endocrinology, 2025)
AimThis study aimed to investigate the association between the serum uric acid to creatinine ratio (SUA/Cr) and long-term target vessel events (TVEs) in diabetes mellitus (DM) patients undergoing percutaneous coronary intervention (PCI) with drug-eluting stents (DES).MethodsFrom July 2009 to August 2011, a total of 2533 patients with coronary heart disease (CHD) who underwent PCI with DES implantation were enrolled to evaluate the relationship between the SUA/Cr and TVEs during a median follow-up of 29.8 months. Multivariable logistic regression and restricted cubic spline analyses were performed, and subgroup analyses were conducted to explore potential effect modifiers.ResultsThe TVEs were significantly associated with previous male gender (OR=1.58, 95%CI: 1.07~2.32, p=0.021), PCI (OR=3.58, 95% CI: 2.27~5.67, p<0.001),previous stroke(OR=2.19,95%CI:1.24~3.89,p=0.007),triglyceride(OR=1.15, 95%CI:1.06~1.26, p=0.002), length of stent (OR=1.01, 95%CI:1~1.01, p<0.001), and diameter of stent (OR=0.62,95%CI:0.41~0.92,p=0.019). In DM patients, Multivariable logistic regression analyses revealed that higher SUA/Cr was independently associated with a reduced risk of TVEs (adjusted OR=0.72, 95% CI: 0.53–0.97, p=0.031). Restricted cubic spline analysis confirmed a linear inverse relationship between SUA/Cr and TVEs (p for non-linearity=0.782). Subgroup analyses revealed stronger protective effects in non-smokers and non-ST elevation acute coronary syndrome (NSTE-ACS) patients within the DM cohort.ConclusionA higher SUA/Cr is independently associated with a reduced risk of TVEs in DM patients undergoing PCI with DES. SUA/Cr holds promise as a potential prognostic biomarker for risk stratification in DM patients undergoing PCI.